PENGARUH TOPIKAL EKSTRA GEL LIDAH BUAYA aloevera KONSENTRASI 10 PERSEN, DAN 20 PERSEN TERHADAP GAMBARAN MAKROSKOPIS LUKA BAKAR GRADE II PADA TIKUS Rattus norvergicus GALUR WISTAR - Riris Wahyu Anggraini; Lenni Saragih; Ni Luh Putu Eka (Jurnal Keperawatan Terapan, 2019)
The acute phase of the burns case is a form of critical trauma with a number of high mortality, Therefore, burn wounds is facing the complexity of problems that need particular attention. Aloe vera contains saponins active substances which are antiseptic and glucomannan as fibroblast growth that can help the healing process. The aim of this research is to examine the Aloe vera extracts toward the healing of burns grade two. The extract is made by maceration using solvent ethanol 70 percent. This research uses white male wistar rats (Rattus norvergicus) who were divided into 4 groups that are given extra aloe vera gel concentration 10 percent aloe vera concentration 20 percent and the control group Silversulfadiazine 1 percent and NaCl 0.9 percent. The observed parameters macroscopic picture (color, extent and presence or absence of exudate).All data is processed and analized statistically using SPSS 23. The results of the statistical analysis Paired Samples T Test and Independent Samples T test showed that the average wound area between NaCl 0,9 percent, Silver Sulfadiazine 1 percent, Aloe vera 10 percent, and Aloe vera 20 percent has no significant difference. Conclusion of this study is Aloe vera 10 percent and 20 percent have the same effect with Silver Sulfadiazine 1 percent for healing of skin burns and applied to humans as an alternative treatment of early burns with a relatively cheap price.